1994
DOI: 10.1139/z94-210
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patch choosing by anthophilous ambush predators: vegetation and floral cues for decisions by a crab spider (Misumena vatia) and males and females of an ambush bug (Phymata americana)

Abstract: Field-collected individuals of Misumena vatia and Phymata americana were compared experimentally as to the kind of vegetation and flower cues they use to choose a hunting site, by introducing them into choice arenas with variously manipulated natural stems of three species of plant and with artificial flowers. Misumena vatia showed a strong preference for stems with flowers or leaves or both; P. americana did not prefer normal stems as strongly and it did not show a statistically significant preference among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 0 publications
0
29
0
4
Order By: Relevance
“…Discrimination among plant species is not unique to Misumenoides. Preferences have also been found in M. vatia and in the ambush bug, Phymata americana (Greco and Kevan 1994), and may be common among anthophilous predators. Discrimination by predatory arthropods among flower patches on the basis of patch size alone has not been documented.…”
Section: Potential Fitness Consequences For Spidersmentioning
confidence: 94%
“…Discrimination among plant species is not unique to Misumenoides. Preferences have also been found in M. vatia and in the ambush bug, Phymata americana (Greco and Kevan 1994), and may be common among anthophilous predators. Discrimination by predatory arthropods among flower patches on the basis of patch size alone has not been documented.…”
Section: Potential Fitness Consequences For Spidersmentioning
confidence: 94%
“…For example, many insects that are useful in biocontrol of pests require florally derived food to mate, find hosts, oviposit and complete their life cycles (Jervis et al, 1993;Ruppert, 1993). There are also anthophiles that use floral sites for capturing prey (Kevan and Baker, 1983;Greco and Kevan, 1994).…”
Section: Pollination Pollinators and Anthophilesmentioning
confidence: 99%
“…Commercially reared bumblebees are an important component of greenhouse tomato production (Kevan et al, 1991c;Kevan, 1994). At least three regionally native species are being used, Bombus terrestris L. in Europe, B. impatiens Cresson in eastern North America, and B. occidentalis Greene in western North America.…”
Section: Introductions and Competitive Interactionsmentioning
confidence: 99%
“…However, we could not confirm positive responses to floral odors or compounds thereof. Greco and Kevan (1994;2001) also reported no discrimination between leaves and flowers by the same spider species. It was shown that M. vatia remains longer on flowers that are frequented by pollinators (Chien & Morse 1998;Morse 2000a) and on flowers that they have experienced before (Morse 2000b).…”
mentioning
confidence: 99%